Role of Non-Invasive Ventilation in Elderly Patients: Therapeutic Opportunity or Medical Futility? An Updated Narrative Review - Francesca Sangiovanni; Giulia Sartori; Nadia Castaldo; Alberto Fantin; Ernesto Crisafulli (Medicina, 2025)
Background and Objectives: Acute respiratory failure (ARF) represents an increasingly relevant clinical challenge in older subjects due to population aging and the high prevalence of cardiopulmonary comorbidities. Non-invasive ventilation (NIV), developed as continuous positive airway pressure (CPAP) or bilevel positive airway pressure (BiPAP), has become a first-line treatment in various forms of ARF, including acute cardiogenic pulmonary oedema (ACPE) and acute exacerbations of COPD (AECOPD), offering several clinical advantages. In this context, the limited evidence on the efficacy of NIV in older patients leaves considerable uncertainty as to whether it constitutes a valid therapeutic option or represents medical futility in these patients. Materials and Methods: This narrative review explores the use of NIV and its outcomes in four key clinical scenarios in the elderly: ARF due to ACPE, AECOPD, community-acquired pneumonia (CAP), and palliative/end-of-life care. Results: Strong evidence supports NIV use with improved outcomes in ACPE and AECOPD, even in older populations. Conversely, data on its use in pneumonia are inconclusive, with potential harm if applied inappropriately. In palliative care, NIV can help relieve symptoms, but if not used appropriately, it may extend suffering. Conclusions: Age alone does not appear to be a sufficient factor to determine whether or not to use NIV; it becomes relevant only when considered in conjunction with the purpose of its use and the patient’s clinical history and condition. Data remain limited and often conflicting, particularly when investigating the elderly population and patients with a “do not intubate” (DNI) order. There is a need for additional research on these patients, focusing on long-term outcomes and quality of life.